A new syndrome of moyamoya disease, kidney dysplasia, aminotransferase elevation, and skin disease associated with de novo variants in RNF213. Issue 7 (7th May 2021) - Strong, Alanna; O'Grady, Gina; Shih, Evelyn; Bishop, Jonathan R.; Loomes, Kathleen; Diamond, Tamir; Hartung, Erum A.; Wong, William; Cuddapah, Sanmati; Cahill, Anne Marie; Hou, Cuiping; Slater, Diana; et al.
Abstract: Ring‐finger protein 213 ( RNF213 ) encodes a protein of unknown function believed to play a role in cellular metabolism and angiogenesis. Gene variants are associated with susceptibility to moyamoya disease. Here, we describe two children with moyamoya disease who also demonstrated kidney disease, elevated aminotransferases, and recurrent skin lesions found by exome sequencing to have de novo missense variants in RNF213 . These cases highlight the ability of RNF213 to cause Mendelian moyamoya disease in addition to acting as a genetic susceptibility locus. The cases also suggest a new, multi‐organ RNF213 ‐spectrum disease characterized by liver, skin, and kidney pathology in addition to severe moyamoya disease caused by heterozygous, de novo C‐terminal RNF213 missense variants.